Pengaruh CEO Duality Terhadap Firm Value Dengan Financial Performance Sebagai Variabel Intervening - Angelia Meysi Setyawan; Devie Deviesa (Business Accounting Review, 2017)
This study aimes to examine and to prove the influence of CEO Duality on Firm Value using Tobin’s Q. This study also used Financial Performance which measured by ROA as an intervening variable. The research was conducted on companies listed in the LQ 45 of 2012-2015 with the samples of 52 companies and measured by using SmartPLS software. The result showed that there was a negative influence of CEO Duality to Firm Value.